Adsorption of Lead by Bentonite Clay (International Journal of Scientific Research and Management (IJSRM), 2017)
Removal of heavy metals from industrial waste water is a worldwide challenge. Inorganic pollutants are difficult to treat as they are non-biodegradable, hence they remain in nature. Such pollutant when enters the food cycle, affect human, plant, animal lives and aquatic systems. Therefore, their removal becomes critical from the environmental point of view. In this study lead is being used as a pollutant in water and unmodified bentonite clay is used as adsorbent material. The bentonite clay was characterized using technique XRD. The results of XRD show that montmorillonite is the main clay mineral. The applicability of the bentonite clay from Bhawnagar area for removal of lead from aqueous solution was tested using the batch process. Experimental parameters affecting the adsorption process like pH value, initial metal concentration, dose of adsorbent (clay), agitation time, and speed were analyzed to get optimum conditions for maximum removal of lead. Experimental data were fitted well to the Langmuir adsorption isotherm with maximum adsorption capacity of 26.3 mg/gram at correlation coefficient of 0.955. It was found that Langmuir adsorption model is fit well with experimental data. Successful application of bentonite clay from Bhawnagar area for removal of lead from aqueous solution greatly supports its field application.